PEMANFAATAN ENERGI SURYA UNTUK MENINGKATKAN EFISIENSI IRIGASI PERTANIAN DI DESA BESAR II TERJUN, KECAMATAN PANTAI CERMIN - Mahyudanil Mahyudanil; Mhd Nuh; Wan Bahroni J Barus; Miranti Miranti; Hemansyah Alam (Universitas Islam Sumatera Utara, 2026)
The implementation of solar energy technology for the irrigation system in Desa Besar II Terjun aims to address the challenges of traditional irrigation, including leakage, high evaporation rates, and dependency on fossil fuels. This technology utilizes solar radiation to power water pumps, thereby reducing operational costs and enhancing water supply stability. The project involves the design, installation, and testing of a solar-powered system equipped with panels, inverters, and storage batteries. An educational and training program for farmers is conducted to ensure effective usage. The results show a 25% increase in irrigation efficiency and agricultural productivity. System evaluation and training indicate success in improving farmers' understanding and productivity. It is recommended to carry out regular maintenance and consider expanding the system to other areas with appropriate technical adaptations.